Prognostic Significance of MYC Rearrangement and Translocation Partner in Diffuse Large B-Cell Lymphoma: A Study by the Lunenburg Lymphoma Biomarker Consortium - Rosenwald, Andreas; Bens, Susanne; Advani, Ranjana; Barrans, Sharon; Copie-Bergman, Christiane; Elsensohn, Mad-Helenie; Natkunam, Yaso; Calaminici, Maria; Sander, Birgitta; Baia, Maryse; Smith, Alexandra; Painter, Daniel; et al. (Journal of clinical oncology, 2019)
rearrangement ( -R) occurs in approximately 10% of diffuse large B-cell lymphomas (DLBCLs) and has been associated with poor prognosis in many studies. The impact of R on prognosis may be influenced by the partner gene (immunoglobulin [IG] or a non-IG gene). We evaluated a large cohort of patients through the Lunenburg Lymphoma Biomarker Consortium to validate the prognostic significance of (single-, double-, and triple-hit status) in DLBCL within the context of the partner gene. The study cohort included patients with histologically confirmed DLBCL morphology derived from large prospective trials and patient registries in Europe and North America who were uniformly treated with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone therapy or the like. Fluorescence in situ hybridization for the , , , and IG heavy and light chain loci was used, and results were correlated with clinical outcomes. A total of 5,117 patients were identified of whom 2,383 (47%) had biopsy material available to assess for -R. -R was present in 264 (11%) of 2,383 patients and was associated with a significantly shorter progression-free and overall survival, with a strong time-dependent effect within the first 24 months after diagnosis. The adverse prognostic impact of R was only evident in patients with a concurrent rearrangement of and/or and an IG partner (hazard ratio, 2.4; 95% CI, 1.6 to 3.6; < .001). The negative prognostic impact of -R in DLBCL is largely observed in patients with double hit/triple-hit disease in which is translocated to an IG partner, and this effect is restricted to the first 2 years after diagnosis. Our results suggest that diagnostic strategies should be adopted to identify this high-risk cohort, and risk-adjusted therapeutic approaches should be refined further.